Accounting Expertise: A Bibliometric Study from 2010 to 2019 in the Main Magazines of Brazil (Global Journal of Management and Business Research, 2021)
The study aims to identify bibliometric characteristics of articles published between 2010 and 2019 on accounting expertise using the Scientific Periodicals Electronic Library SPELL database The methodology used in the research is characterized as a bibliometric descriptive and qualitative research The data were collected from that database where 17 articles were found that contained the keyword Per ciaCont bil which were produced by 49 authors most of whom were co-authored by two authors from the Midwest region of the city of Bras lia-DF and of the teaching institution UniversidadeCat lica de Bras lia UCB The articles are distributed in 12 magazines and there is practically no publication in those considered to be of high impact having as the most discussed subject general aspects of accounting expertise despite the importance of this area of practice of the accounting professional there are few publications on the subject It is suggested therefore that future research will be developed on the theme accounting expertise
Keywords: bibliometric data baseaccounting expertise